Improving Teacher Performance in Elementary Schools: The Role of Democratic Leadership and Principal Performance - Sri Rahayu Rahayu; Hartono; Muslim Afandi (Institut Agama Islam An-Nawawi Purworejo, 2025)
Teacher performance is a key factor in improving the quality of education, but there are still many challenges faced regarding the role of principal leadership in encouraging teacher professionalism. This study aims to determine the influence of teacher perceptions of the principal's democratic leadership style and the principal's performance on teacher performance in elementary schools. The research method used is quantitative with a survey design. The study population was 65 teachers from five elementary schools in Tapung District who were selected through random sampling techniques using the Slovin formula. Data were collected using a Likert scale questionnaire (1–4) and analyzed using multiple linear regression with the help of SPSS version 25. The results showed that teacher perceptions of the principal's democratic leadership style had a significant effect on teacher performance (t count = 3.879 > t table = 2.034; sig. = 0.004), as well as the principal's performance which also had a significant effect on teacher performance (t count = 5.875 > t table = 2.034; sig. = 0.000). Simultaneously, the two independent variables contributed 57.5% to teacher performance, while the remaining 42.5% was influenced by factors outside this study. In conclusion, democratic leadership style and principal performance play a significant role in improving teacher performance, thus strengthening the theory of participatory leadership while providing practical implications for improving the quality of basic education.